Hubungan Asupan Zat Gizi Makro Dengan Status Gizi Balita (INCH : Journal of Infant and Child Healthcare, 2025)
Toddlers are a group vulnerable to nutrition that is easily affected by health problems or prone to malnutrition. This type of research is quantitative with a cross-sectional study approach. The location of the study was conducted at the Morella Village Hall, Central Maluku Regency. The number of samples was 63 toddlers aged 7-59 months. Data analysis was carried out using the Fisher Exact test. In the analysis of nutrient intake with nutritional status based on BB/U, TB/U, and BB/TB, the p-value did not have a significant relationship, p ≥ 0.05. Toddlers with malnutrition are the result of children suffering from an infectious disease. With sufficient nutritional intake, energy needs can be met. The deficiency in this study was that an assessment of infectious diseases was not carried out. The results of the test of the relationship between macronutrient intake and nutritional status of toddlers showed there was no significant relationship.